Additional lung – a rare malformation - S. A. Karavaeva; A. V. Podkamenev; T. V. Patrikeeva; M. M. Aleshugin; M. V. Golubeva; А. G. Li; R. A. Ti; D. A. Malekov; A. I. Tashchilkin; O. A. Murashova (Вестник хирургии имени И.И. Грекова)
Additional lung is an extremely rare malformation. At an early age the course is often asymptomatic, but sometimes the additional lung may lead to life-threatening clinical manifestations. In these cases, early surgical treatment is required. We describe our own clinical cases with histological verification of the diagnosis of «Additional lung», the timing and algorithm of postnatal radiation examination, the method of treatment.